Perancangan Sistem Informasi Desa Berbasis Website di Desa Pandean Kecamatan Gondang Kabupaten Nganjuk - Hendra Maulana; Richul Munawaroh; Nurmanida Azizah Nuha; Diva Faridathul Ilmi; Muhammad Fabbian Rachmansyah; Alif Syahda Adji Masyuri; A. Malik Haramain (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
E-Government is an information system that is very widely used today in line with the development of information and communication technology. Realizing the huge benefits of information technology that is developing today, a new system is needed that must be implemented in Pandean Village. Therefore, observations and focus group discussions were carried out with village officials and community representatives so that the author could find out what needs and information should be included on the website. With the implementation of the E-Government system, it is expected to have a relatively good and beneficial impact on all interested parties.